ANALISIS FUNDAMENTAL TERHADAP CORPORATE SOCIAL RESPONSIBILITY (Studi padaPerusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia periode 2013-2016) - Nur Chorika Zarina Saraswati, 14.05.52.0036; Susilowati, Yeye (Students' Journal of Accounting and Banking, 2018)
This study aims to examine and analyze the effect of profitability, leverage, liquidity and company size on corporate social responsibility on mining companies listed on the Indonesia Stock Exchange in 2013-2016. The population in this study are mining companies listed on the Indonesia Stock Exchange in 2013-2016. The samples were taken using the purpose sampling method and obtained 88 observational data from 42 companies. The data analysis method used is a multiple linear regression data analysis method with SPSS 21 program and uses secondary data in the form of a Sustainability Report. Based on the research that has been done, the results obtained that Profitability and Size have a significant positive effect on Corporate Social Responsibility. While Leverage has a negative and not significant effect on Corporate Social Responsibility and Liquidity, it does not have a significant positive effect on Corporate Social Responsibility. Keywords: Profitability, Leverage, Liquidity, Corporate Size and Corporate Social Responsibility.